Design and Implementation of an Improved Two Rate Three Color Meter (ITRTCM) Algorithm for Quality of Service Admission Control Using UDP as Traffic Agent ? (European Journal of Engineering Science and Technology, 2018)
This paper designed an Improved Two Rate Three Color Meter (ITRTCM) algorithm to get more packets operating above PIR across the Internet for better QoS assurance. The design and simulation of the network model for implementing ITRTCM algorithms on User Datagram Protocol (UDP) as traffic agents on the Internet were done using NS-2. The throughput, loss rate, fairness rate, and one-way packet delay were used as performance metrics. The results for UDP as a traffic agent revealed that ITRTCM and TRTCM had a throughput of 50463 and 50460; fairness rate of 0.2726 and 0.2632; loss rate of 74.59 and 74.70; and one-way packet delay of 0.8584ms and 0.8669ms respectively. The proposed ITRTCM algorithm outperforms the existing TRTCM algorithm in terms of the aforementioned metrics.